2017
DOI: 10.12659/ajcr.903345
|View full text |Cite
|
Sign up to set email alerts
|

ST-Segment Elevation Myocardial Infarction with Acute Stent Thrombosis Presenting as Intractable Hiccups: An Unusual Case

Abstract: Patient: Male, 51Final Diagnosis: ST-segment elevation myocardial infarction with acute stent thrombosisSymptoms: Chest pain • hiccupsMedication: —Clinical Procedure: —Specialty: CardiologyObjective:Unusual clinical courseBackground:Acute coronary syndrome (ACS) can present with atypical chest pain or symptoms not attributed to heart disease, such as indigestion. Hiccups, a benign and self-limited condition, can become persistent or intractable with overlooked underlying etiology. There are various causes of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In a case reported by Davenport et al in 2012, similar to our case, the patient presented with persistent hiccups without any other complaints; however, the patient was found to have inferior wall NSTEMI, and a subsequent cardiac catheterization revealed significant stenosis of the left circumflex and first obtuse marginal coronary arteries [9]. Zhang et al reported a case of persistent hiccups with chest pain in a patient with cocaine-induced inferior wall STEMI with 99% occlusion of the mid-RCA and 80% stenosis of the LAD artery [4]. …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In a case reported by Davenport et al in 2012, similar to our case, the patient presented with persistent hiccups without any other complaints; however, the patient was found to have inferior wall NSTEMI, and a subsequent cardiac catheterization revealed significant stenosis of the left circumflex and first obtuse marginal coronary arteries [9]. Zhang et al reported a case of persistent hiccups with chest pain in a patient with cocaine-induced inferior wall STEMI with 99% occlusion of the mid-RCA and 80% stenosis of the LAD artery [4]. …”
Section: Discussionsupporting
confidence: 64%
“…Any irritants in the reflex pathway, such as physical, chemical, inflammatory, or neoplastic process, can trigger hiccups. Most commonly, persistent hiccups are caused by the nervous system disorder, either central (neoplastic and inflammatory) or peripheral by irritation of the phrenic nerve (goiter) or irritation of the vagus nerve (otolaryngologic diseases, meningitis, esophageal, stomach, and duodenal diseases, hepatitis, pancreatitis, and enteritis) [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Other sites of referred pain are the mandible, temporomandibular joint, ears, neck, and teeth [ 5 ]. Hiccups, a rare presenting symptom, was reported in a patient with PCI (percutaneous coronary intervention)-related STEMI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,18 Of the myocardial infarction group, one patient each was diagnosed with Dressler syndrome, 16 associated with ischemic cardiomyopathy and atrial fibrillation, 15 and had in-stent thrombosis of the right coronary artery. 29 In one patient, myocardial infarction was chronic with a 4-year medical history, 15 and another patient had a 2-year history of myocardial infarction with an acute onset at current presentation. 26 Except for these two patients, all remaining patients had AMI.…”
mentioning
confidence: 99%
“…The underlying etiology was myocardial infarction in 127 (98.4%) patients, 5,[7][8][9][10][11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29] and myocardial ischemia in 2 (1.6%) patients. 6,18 Of the myocardial infarction group, one patient each was diagnosed with Dressler syndrome, 16 associated with ischemic cardiomyopathy and atrial fibrillation, 15 and had in-stent thrombosis of the right coronary artery.…”
mentioning
confidence: 99%